Capillary straightening processes as a contextualizer theme for Organic Chemistry teaching (Research, Society and Development, 2020)
The use of themes related to students' daily lives in the teaching of scientific concepts in basic and higher education subjects, promoting contextualization, is an action that contributes greatly in improving the quality of teaching. The concepts usually explored by the Organic Chemistry teaching serve this parameter, as they fail to gain prominence when they are not linked to the student's reality or taught without the use of mechanical models or adequate computational resources. This study was developed in this context, from the disciplines Organic Chemistry I and II of the Chemistry Graduation course from the Federal University of Mato Grosso - CUA, Brazil. The objective was to explore the theme “Hair Straightening Processes” in the scientific literacy of students through Organic Chemistry content. The methodology involved conceptual bibliographic research on the subject in different databases, focusing on four straightening techniques: with ammonium thioglycolate, formaldehyde, glyoxylic acid and carbocysteine. In addition to inter-area approaches to the theme, such as aspects related to health, detailed mechanistic proposals were raised for each of the processes, with the intention of justifying how these substances chemically act on hair fibers, since they are vaguely described in the literature. The results showed the relevance of the context for the understanding of the studied concepts, and the contents of Organic Chemistry gained more meaning and fluidity with the adopted proposal, encouraging students in the search for propositions and interconnection of chemistry with other areas.